(untitled) (Global Journal of Computer Science and Technology, 2011)
In this paper we propose and design key authentication protocols for wireless networks. We consider three mobile service domains; each has an authentication server. We denote by D1, D2 and D3 corresponding authentication servers. For simplicity, let D1, D2 ,D3 represent those three domains. This mobile system can provide mobile communication services to a large number of users. For simplicity, we assume three users (A, B and C) in the system only, where A has registered with D1 and B has registered with D2 and C has registered with D3.